Identification of a Novel Small Non-Coding RNA Modulating the Intracellular Survival of Brucella melitensis - Wang, Yufei; Ke, Yuehua; Xu, Jie; Wang, Ligui; Wang, Tongkun; Liang, Hui; Zhang, Wei; Gong, Chunli; Yuan, Jiuyun; Zhuang, Yubin; An, Chang; Lei, Shuangshuang; et al. (Frontiers in Microbiology, 2015)
Bacterial small non-coding RNAs (sRNAs) are gene expression modulators respond to environmental changes, stressful conditions, and pathogenesis. In this study, by using a combined bioinformatic and experimental approach, eight novel sRNA genes were identified in intracellular pathogen Brucella melitensis. BSR0602, one sRNA that was highly induced in stationary phase, was further examined and found to modulate the intracellular survival of B. melitensis. BSR0602 was present at very high levels in vitro under stresses similar to those encountered during infection in host macrophages. Furthermore, BSR0602 was found to be highly expressed in the spleens of infected mice, suggesting its potential role in the control of pathogenesis. BSR0602 targets the mRNAs coding for gntR, a global transcriptional regulator, which is required for B. melitensis virulence. Overexpression of BSR0602 results in distinct reduction in the gntR mRNA level. B. melitensis with high level of BSR0602 is defective in bacteria intracellular survival in macrophages and defective in growth in the spleens of infected mice. Therefore, BSR0602 may directly inhibit the expression of gntR, which then impairs Brucellae intracellular survival and contributes to Brucella infection. Our findings suggest that BSR0602 is responsible for bacterial adaptation to stress conditions and thus modulate B. melitensis intracellular survival.